Analisis Tindak Tutur Ilokusi Video “Sex Education” pada Saluran YouTube Neuron - Savira Nailil Hana; Rizna Asticka; Noufal Azmi Widianto; Esti Maurilla; Firas Abid Zidan; Asep Purwo Yudi Utomo; Amilia Buana Dewi Islamy; Rina Rina (Lembaga Pengembangan Kinerja Dosen, 2025)
Humans as social creatures need language as a communication tool to share thoughts, feelings, and information. Language is a complex social phenomenon that is influenced by culture and social context. Pragmatics, which is a branch of linguistics that studies meaning in context, focuses on speech acts as a basic element in communication. This study aims to analyze the illocutionary speech acts (directive, expressive, commissive, declarative, and representative) that often appear on Neuron's YouTube channel, especially on playlists related to sex education. This research uses descriptive qualitative method and pragmatics theoretical approach, and collects data through literature study by referring to various scientific literatures relevant to the topic discussed. The focus of the study is to analyze the illocutionary speech acts in sex education videos on Neuron's YouTube channel, which discuss important issues such as HIV/AIDS, contraception, and transgender. Of the six videos in the “Sex Education” playlist analyzed, 91 illocutionary speech acts were found, consisting of 28 directive speech acts, 8 expressive speech acts, 11 commissive speech acts, 15 declarative speech acts, and 29 representational speech acts. This research is expected to provide insight into the use of illocutionary speech acts in Neuron's YouTube channel playlist and help viewers understand the messages conveyed in these sex education videos.